Study of Current Trends in the smart Healthcare Sector using IoT - Shrivastava, Mani; Sahu, Neelam (International Journal of Computer Sciences and Engineering, 2020)
The Internet of Things is changing our lives with their increasing multidisciplinary applications. Applications of IoT are growing day by day in the smart healthcare sector. The wide range of applications of IoT includes healthcare services. In our daily life, traffic monitoring, healthcare, security, transport and logistics are major sectors for the study of applications of IoT. In smart healthcare sector, applications of IoT connect smart devices, machines, patients, doctors and sensors to the Internet. Healthcare is becoming a major socio-economic concern when it comes to health expenditure, the need and availability of resources and personal care, especially for the elderly in society. Efficiently and intelligently trends in healthcare are enabling physicians to provide remote monitoring, chronic disease management and elderly care of distant patients, and even care for institutional patients after being connected to the Internet. This article paper examines the various smart healthcare trends that have transformed traditional healthcare systems by makinghealthcare management more efficient through their applications.